EFL Teacher Strategies for Reducing Student Anxiety in Learning English - Syahrunnisa, Syahrunnisa; Atmowardoyo, Haryanto; Sunra, La (Celebes Scholar pg, 2023)
This research aims at identifying the measures that EFL teachers take to minimize learners’ anxiety in English learning at MA Arifah Indonesia particularly from the aspect of anxiety and second language acquisition. The study adopted a concurrent triangulation design in which quantitative data was collected from the questionnaires while qualitative data was collected from interviews. The study shows that anxiety arising from fear of negative evaluation, communication apprehension, and test, hurts the students’ performance in speaking activities and academic achievement. Most of the students benefited from approaches adopted by the teacher such as behaviour modification and support from classmates and Gradualiliarly Increasing the Task Difficulty. But as the results of the students’ feedback reveal, it is not enough for the students, especially those with higher levels of anxiety, to employ these methods; therefore, they require other kinds of interventions, including practices based on mindfulness. The study also brings out the impact of worry on test performance, and there is a need to analyse the existing strategies of assessments to provide for the worried students. Such results suggest that EFL education needs to be more comprehensive to include psychological intervention into learners’ mental state and teaching methods that are best suited for these learners in order to introduce change for a better learning environment.